TEACHERS’ PERCEPTIONS ON THE NEED FOR E-LKPD TO ENHANCE HOTS IN PARTICLE KINEMATICS - Tanti Febrianti; Kistiono, Kistiono; Wiyono, Ketang (EduFisika: Jurnal Pendidikan Fisika, 2026)
This study looks at how students think critically in physics specifically in particle kinematics. We want to know what teachers think about students thinking skills. We also want to see if schools have the technology to help students learn. We want to find out if we need to create digital worksheets for students. We asked 53 high school physics teachers in Ogan Ilir Regency to answer some questions. We used a kind of questionnaire that asked teachers to agree or disagree with some statements. The results show that students are not very optimally at analyzing, evaluating and creating. For C4, 47–57% of teachers somewhat agreed that students possess analytical skills, indicating limited mastery. For C5, 53% of teachers disagreed that students are capable of evaluation, while for C6, 51–53% disagreed that students have creating skills and 11% strongly disagreed that students are able to produce independent work. In contrast, technological support was considered adequate, with 86% of teachers stating that school facilities are sufficient and 100% supporting the use of technology in learning. Additionally, 72% of teachers have used E-LKPD and 96% perceived it as practical. Notably, all respondents (100%) expressed the need for HOTS-based E-LKPD in particle kinematics. These findings highlight the urgency of developing contextually relevant and systematically designed E-LKPD. The novelty of this study lies in integrating empirical data on HOTS, technological readiness, and instructional needs as a basis for developing effective physics learning resources.